CLUSTERING DATA NILAI SISWA SMA UNTUK PENENTUAN JURUSAN MENGGUNAKAN ALGORITMA FUZZY C-MEANS - Fajar Akbar (Jurnal Techno Nusa Mandiri, 2015)
Determination of the majors a process that occurs at the time the class- X will go up to class- IX, this is because the addition proses are carried out must be based in the interests and talent of each student’s.In addition, this process is done by Bp/Bk, witch this assessment process based on value evaluation of each subject’s flagship from each Department, to major in Science related subject (biology, physics, chemistry, mathematics), to social sciences Departement (economics, sociology, geography, history), and for the Departement of IPB (Indonesian Language, English, Germany Language).In this reaseach, FCM Clustering can assist and improve value for Determination of the majors' process 72%.